2015
DOI: 10.1021/acssuschemeng.5b00844
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Cross-Linked Lignin-Based Polymer: Modification, Characterization, and Flocculating Performance in Humic Acid Coagulation

Abstract: In this study, a lignin-based flocculant (LNF) was synthesized by grafting amine groups into alkali lignin containing papermaking sludge. Characterization of LNF, such as FTIR, zeta potential, cationic degree, viscosity, and molecular weight, showed that the product was a cationic polymer with high solubility. LNF was used with aluminum sulfate (AS) and polyaluminum chloride (PAC) in humic acid coagulation to demonstrate its efficiency. Coagulation behavior and floc properties of LNF+PAC and LNF +AS dual-coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 37 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…However, this method is inefficient for removing low molecular weight and hydrophilic compounds from wastewater [ 33 ]. To address this problem, Li and coworkers [ 34 ] synthesized a sludge-based flocculant by grafting amine groups onto the organics of sludge ( Figure 2 ). The sludge contained a major portion of lignin, and thus the chemical structure of lignin was considered for describing its reaction mechanisms with other chemicals in Figure 2 .…”
Section: Flocculantmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method is inefficient for removing low molecular weight and hydrophilic compounds from wastewater [ 33 ]. To address this problem, Li and coworkers [ 34 ] synthesized a sludge-based flocculant by grafting amine groups onto the organics of sludge ( Figure 2 ). The sludge contained a major portion of lignin, and thus the chemical structure of lignin was considered for describing its reaction mechanisms with other chemicals in Figure 2 .…”
Section: Flocculantmentioning
confidence: 99%
“…The AS and PAC were used for improving the efficiency of flocculation in a dual system. The results showed that the product could be used as a flocculant in this system and its efficiency was 25% higher under acidic conditions [ 34 ].…”
Section: Flocculantmentioning
confidence: 99%
See 1 more Smart Citation
“…After grafting ESO onto EHLA to form EHL-ESO, the peaks at 1600, 1741, and 3409 cm −1 shifted to the lower wavenumbers at 1566, 1725, and 3376 cm −1 , respectively, indicating that ESO was successfully introduced onto EHLA. Moreover, a new peak appeared at 1643 cm −1 , corresponding to the bending vibration of N-H, 27 and a peak at 722 cm −1 disappeared, belonging to the bending (rocking) of –(CH 2 ) n – and –HC CH–. 26 Peak intensities at 825 and 843 cm −1 (epoxy group) 26 decreased and shifted to higher wavenumbers at 838 and 877 cm −1 , respectively, indicating that a ring-opening reaction occurred between amino groups (EHLA) and epoxy groups (ESO).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, LN is the second largest natural polymer and largely exists in black liquor in paper manufacturing 22 . In fact, LN and its derivatives after some chemical modifications have been widely applied in water treatment, which could be used as adsorbents, flocculants, and scale inhibitors 23,24 . As effective adsorbents due to their having abundant oxygen-containing functional groups, lignin-based materials were employed to remove various contaminants in water such as heavy metals 25,26 and cationic dyes 27,28 in previous study.…”
Section: Introductionmentioning
confidence: 99%